Pattern of Foreign Body Presentation in an ENT Outpatient Clinic in South Eastern Nigeria - EE, Afiadigwe; US, Umeh; PO, Ebiringa; JU, Obah; ND, Ukpai; I., Nwafor (International Journal of Innovative Research in Medical Science, 2022)
Background: Foreign bodies (FBs) in the ear, nose and throat are about the commonest emergencies encountered in otorhinolaryngological practice. Prompt and successful removal in the clinic obviates the need for general anaesthesia and reduces undue morbidity and mortality. Aim and Objectives: To profile all the cases of FBs that presented to our ENT outpatient clinic between the period of July 2011 and August 2021. Methodology: This was a retrospective study of the cases FBs that presented as outpatient at Eastern Specialist Surgical Clinics, Nnewi over a period of 10 years. All FBS requiring general anaesthesia or operating room procedures were excluded from this study. The data was analyzed using SPSS version 23. Results: Out of a total of 11,440 patients seen within the study period, 807 were managed for FBs, giving a prevalence of 7.1%. 51.4% of the patients were females, while 48.6% were males. Age of the participants was summarized using median (Interquartile range); 4 (3-13Years). Children aged between 1-5 years of age were the majority (59.1%), while the age categories least represented were those between 16-20years and 31-35years (2.6% each). Majority of the FBs were removed from the ears (69.8%), followed by the nose (28.4%). Others were tonsils (0.9%), Oropharynx (0.6%), palate (0.2%) and the tongue (0.1%). The various types of FBs removed in this study are as follows; Beads (18.1%), cotton buds (17%), insects (9.4%), pencil eraser (5.7%), foam (5.1%). All the FBs were successfully retrieved in the clinics with patient awake but under adequate restraints or cooperation in older individuals as the case may be. Conclusion: This study has shown the pattern of presentation of FBs at ENT outpatient clinics in our environment. With requisite expertise, equipment and adequate restraint or cooperation, most FBs could be removed without general anesthesia.